SOCIAL INTERMEDIATION OF SHARIA BANKING FROM THE ISLAMIC LAW PERSPECTIVE: A Case Study at Bank Negara Indonesia (BNI) Syari’ah - Ipandang Ipandang; Andi Novita Mudriani Djaoe (ULUL ALBAB Jurnal Studi Islam, 2022)
This research focuses on the dynamics of social intermediation implemented by BNI Syari’ah in Kendari City, South Sulawesi, Indonesia based on the Islamic law perspective and its impact on social life. In developing and realizing the social intermediation function of Islamic banks that arise from administrative-structural and cultural dimensions, the interpretation and meaning of a conceptual perspective are present. Therefore, this research applies a qualitative approach with a case study type through a one-site design. Data collection is done through in-depth interviews, participatory observation, and documentation study. The data were analyzed with the principle of on-going analysis using Miles and Huberman's analysis method. The research found that social intermediation implemented by BSK (BNI Syari’ah Kendari) really determines the potential and mentality of the poor society. This social intermediation is in the form of institutions such as the bayt al-mâl. This way, the poor can receive zakât, infâq, alms, grants, and other social funds. Furthermore, the social intermediation even has a positive impact on the community, because it integratively puts forward the concept of maslahah (according to the principles of maqâsid al-sharî‘ah).